A review of Sadyattes Stål, 1875, with the descriptions of six new species from the Philippines (Phasmatodea: Platycraninae: Stephanacridini) - Hennemann, Frank H. (Zootaxa, 2025)
The genus Sadyattes Stål, 1875 is a poorly understood clade of stick insects of the subfamily Platycraninae and tribe Stephanacridini, that currently comprises three species from Borneo as well as type-species S. borrii Stål, 1875 whose locality is as yet a mystery. In its present recognition the genus is here shown to be paraphyletic and research has revealed that a number of species currently attributed to other genera, one of which is not even closely related, actually belong in Sadyattes. To elucidate these shortcomings a taxonomic review of Sadyattes at the species level is presented along with a generic redescription. Sadyattes is distributed throughout the land masses of the Sunda Shelf (Borneo, Peninsular Malaysia, Java and Sumatra with some of its surrounding islands) and the Philippine Islands. Differential diagnoses as well as notes on intraspecific variability and the distributions are provided for all known species, including new descriptions and combinations, with most species also illustrated. Keys are presented to distinguish females and males. The genus Eucarcharus Brunner v. Wattenwyl, 1907 is found to be a synonym of Sadyattes and thus synonymised (syn. nov.). The two Philippine species previously contained in Eucarcharus, E. fallax Brunner v. Wattenwyl, 1907 and E. feruloides (Westwood, 1859), are automatically transferred to Sadyattes, which results in two new generic combinations (comb. nov.). Four species are transferred to Sadyattes from other genera, which results in another four new generic combinations (comb. nov.): the Bornean S. decoris (Seow-Choen, 2016) and S. incertus (Brunner v. Wattenwyl, 1907) from Peninsular Malaysia, Bangka Island and the Andaman Islands from the genus Phobaeticus Brunner v. Wattenwyl, 1907 (Clitumninae: Pharnaciini), the Bornean S. nigricornis (Redtenbacher, 1908) from the genus Pharnacia Stål, 1877 (Clitumninae: Pharnaciini), and the Philippine S. leytensis (Zompro, 1997) from the genus Hermarchus Stål, 1875 (Platycraninae: Stephanacridini). Six new species from the Philippines are described: S. banwaon sp. nov. from the island of Mindanao from the female, S. maganda sp. nov. from the island of Mindoro from the female and male, S. matipuno sp. nov. from the island of Luzon from the female, male and egg, S. mindanaense sp. nov. from the island of Mindanao from the female, male and egg, S. panayense sp. nov. from the island of Panay from the female only, and S. tubaense sp. nov. from the island of Luzon from the male. A redescription of the male of the type-species S. borrii Stål, 1875 is presented, whose distribution is here shown to comprise Java and Sumatra, along with a description of the previously unrecorded female, which has proven to be represented by Nesiophasma zanus Hennemann, 1998 (syn. nov.). This latter synonymy renders the questionable locality “New Guinea” of Nesiophasma zanus as erroneous. The previously unknown males of S. feruloides comb. nov., S. fallax comb. nov., and S. incertus comb. nov. are described and those of the latter two species are illustrated for the first time. Also, the eggs of S. fallax comb. nov. and S. feruloides comb. nov. are described and illustrated for the first time. Nearchus grubaueri Redtenbacher, 1908 is re-synonymised with S. incertus (Brunner v. Wattenwyl, 1907; rev. syn.). Holotypes of the newly described species are deposited in the collections of Institute Royal des Sciences Naturelles de Belgique, Brussels, Belgium (RBINS) and the Natural History Museum, London, U.K. (NHMUK).